2022
DOI: 10.1038/s41467-022-28922-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion interface layer controlling the acceptor phase of bilayer near-infrared polymer phototransistors with ultrahigh photosensitivity

Abstract: The narrow bandgap of near-infrared (NIR) polymers is a major barrier to improving the performance of NIR phototransistors. The existing technique for overcoming this barrier is to construct a bilayer device (channel layer/bulk heterojunction (BHJ) layer). However, acceptor phases of the BHJ dissolve into the channel layer and are randomly distributed by the spin-coating method, resulting in turn-on voltages (Vo) and off-state dark currents remaining at a high level. In this work, a diffusion interface layer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Figures a and S10a show that the dark current of the ternary system was 2–3 orders of magnitude lower than that of the binary system (@ V g = 0 V), indicating that PS doping could decrease the dark current of the NIR device. It should be noted that the dark current of NIR phototransistors is caused by the continuous injection of carriers from the electrode. ,, Hence, PS is assumed to isolate the donor/acceptor, and its insulation property increases the resistance to carrier injection from the electrode. Additionally, Figure b shows that the photocurrent of the ternary system was 1 order of magnitude higher than that of the binary system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures a and S10a show that the dark current of the ternary system was 2–3 orders of magnitude lower than that of the binary system (@ V g = 0 V), indicating that PS doping could decrease the dark current of the NIR device. It should be noted that the dark current of NIR phototransistors is caused by the continuous injection of carriers from the electrode. ,, Hence, PS is assumed to isolate the donor/acceptor, and its insulation property increases the resistance to carrier injection from the electrode. Additionally, Figure b shows that the photocurrent of the ternary system was 1 order of magnitude higher than that of the binary system.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, high-performance bilayer NIR phototransistors were successfully prepared by forming an acceptor diffusion interface instead of an immiscible interface to regulate electrons. The results showed that V o decreased from 26 V to zero, and the photosensitivity ( I ph / I dark ) increased from 22 to 1.7 × 10 7 …”
Section: Introductionmentioning
confidence: 96%
“…N2200) always have a wide bandgap. [20][21][22][23] Therefore, it is of great significance to develop novel semiconducting polymers with new conjugated backbones to further narrow the bandgap. In addition to the rational design of novel semiconducting polymers, the doping effect can also efficiently tune the properties of semiconducting polymers, and broaden the absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] In particular, NIR phototransistors can convert NIR light into electrical signals, realizing the detection of NIR light. [10][11][12][13][14][15][16][17] Traditional NIR phototransistors are mainly based on inorganic semiconductor materials, which nevertheless have the disadvantages of high cost and temperature sensitivity. 18 Benefiting from the characteristics of light weight, flexibility and solution processibility, organic semiconductors are ideal candidates for NIR light detection.…”
mentioning
confidence: 99%